URGENT PROBLEMS IN THE TEACHING OF ANATOMY IN THE DIRECTION OF TREATMENT OF THE MEDICAL INSTITUTION - Sharipov Abdulaziz Abduraimovich; Turg‘unova Shaxnoza Tursunovna (Bright Mind Publishing, 2025)
The teaching of anatomy plays a crucial role in medical education, particularly in the direction of treatment. However, several urgent problems hinder its effectiveness. These include outdated teaching methods, insufficient practical training, lack of integration with modern technologies, and challenges in student comprehension. This article examines these issues in-depth and proposes potential solutions to enhance the teaching of anatomy in medical institutions.
Keywords: Anatomy education, medical curriculum, practical training, digital tools, pedagogical methods, medical students.